2011
DOI: 10.1124/dmd.111.039164
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, Metabolism, Distribution, and Excretion of Carfilzomib in Rats

Abstract: Carfilzomib [(2S)-N-[(S)-1-[(S)-4-methyl-1-[(R)-2-methyloxiran-2-yl]-1-oxopentan-2-ylcarbamoyl]-2-phenylethyl]-2-[(S)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 30 publications
12
112
0
1
Order By: Relevance
“…However, there was a significant correlation between inhibition of CT‐L activity and ProCISE in whole blood and PBMCs for the aggregate of paired samples (Table SII). Inhibition levels were also equivalent in patients with MM receiving 20 mg/m 2 carfilzomib as a 2‐ to 10‐min or 30‐min infusion, which is consistent with results reported in animals (Yang et al , 2011). It is noteworthy that the overall level of CT‐L inhibition seen with carfilzomib is higher than the 65–70% inhibition rate reported in bortezomib‐treated patients (Orlowski et al , 2002; Papandreou et al , 2004; Moreau et al , 2008).…”
Section: Discussionsupporting
confidence: 89%
“…However, there was a significant correlation between inhibition of CT‐L activity and ProCISE in whole blood and PBMCs for the aggregate of paired samples (Table SII). Inhibition levels were also equivalent in patients with MM receiving 20 mg/m 2 carfilzomib as a 2‐ to 10‐min or 30‐min infusion, which is consistent with results reported in animals (Yang et al , 2011). It is noteworthy that the overall level of CT‐L inhibition seen with carfilzomib is higher than the 65–70% inhibition rate reported in bortezomib‐treated patients (Orlowski et al , 2002; Papandreou et al , 2004; Moreau et al , 2008).…”
Section: Discussionsupporting
confidence: 89%
“…However, despite the excellent efficacy observed in preclinical models of solid cancer (Yang et al, 2006;Demo et al, 2007;Ao et al, 2012), CFZ demonstrated disappointing results clinically when tested in patients with advanced solid tumors . Although the exact mechanisms underlying the discrepancies between the preclinical and clinical observations are currently unknown, one potential explanation is the rapid metabolic degradation of CFZ in vivo (Yang et al, 2011). CFZ degradation in humans is mainly due to peptide cleavage and epoxide ring opening, resulting in plasma half-life of less than 30 minutes .…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies in rats and monkeys have shown that carfilzomib is rapidly and extensively distributed and potently inhibits proteasome activity in a variety of tissues after i.v. administration (Yang et al, 2011). Carfilzomib has a systemic clearance (CL) greater than hepatic blood flow and a terminal half-life (t 1/2 ) shorter than 30 minutes.…”
Section: Introductionmentioning
confidence: 99%